Effect of the sedative drug zolpidem tartrate on the immature and mature stages of carrion flies Chrysomya rufifacies and Chrysomya indiana - Lamya Ahmed Al-Keridis (Elsevier, 2022)
In forensic investigations many types of evidence are collected, such as urine, blood, and gastric contents. Carrion insects may also be recovered. Entomotoxicology is an approach to detecting, identifying, and quantifying chemicals in an investigation involving a death. Entomotoxicology involves the toxicological analysis of the tissues of insects recovered from a corpse. Cadaveric flies ingest chemicals contaminating the tissue and fluid on which they feed, affecting their physiology, growth, and development. We evaluated the effect of Zolfresh (zolpidem tartrate) on the development rate and growth parameters of two Calliphorid flies, Chrysomya rufifacies (Macquart, 1842) and Chrysomya indiana (Abd Algalil & Zambare, 2016). The two species of Calliphoridae were fed with fresh chopped liver treated with various concentrations of Zolfresh. We evaluated the way in which the chemical affected the morphological parameters and developmental rates of C. indiana and C. rufifacies. The rate of development in the flies was negatively correlated with the concentration of Zolfresh. The results of the study concurred with those of several studies on the same and different species of Calliphoridae. The experimental data were used to estimate insect-based postmortem interval values. In real forensic examination, this estimation can be compromised by prior use of drugs.